2008
DOI: 10.1007/s11605-007-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete Endoscopic Closure of Gastric Defects Using a Full-Thickness Tissue Plicating Device

Abstract: Obtaining endolumenal closure of hollow visceral defects may complement conventional, incision-based, surgical alternatives and benefit the experimental field of natural orifice translumenal endoscopic surgery (NOTES). Endoscopic tissue plicating devices (TPD) represent a promising closure technology; however, the long-term integrity of resultant closures is uncertain. Swine (n=10) underwent survival transgastric NOTES peritoneoscopy procedures with TPD gastrotomy closure while device performance and closure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…In addition to GERD treatment, the Plicator device can be used for endoluminal suturing of gastrointestinal (GI) wall perforations or for natural orifice transluminal endoscopic surgery (NOTES) gastrotomy closure [50][51][52][53][54]. A recent study evaluating the Plicator with modified pledgets and resorbable sutures demonstrated successful and reliable NOTES gastrotomy closure in an animal survival trial [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to GERD treatment, the Plicator device can be used for endoluminal suturing of gastrointestinal (GI) wall perforations or for natural orifice transluminal endoscopic surgery (NOTES) gastrotomy closure [50][51][52][53][54]. A recent study evaluating the Plicator with modified pledgets and resorbable sutures demonstrated successful and reliable NOTES gastrotomy closure in an animal survival trial [55].…”
Section: Discussionmentioning
confidence: 99%
“…Because the device enables rapid and easy placement of leakproof transmural sutures with serosal apposition, the device seems suitable for closure of GI wall defects or NOTES gastrotomy. For reliable NOTES gastrotomy or perforation closure, a transmural suturing device enabling serosal apposition is of fundamental importance to achieve reliable closure strength [51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The NOTES gastrotomy finally was closed with an endoscopic tissue plicating device (NDO Plicator; NDO Surgical, Mansfield, MA, USA) using a technique developed and reported by our group [9,10]. Briefly, two or three pledgeted suture implants were deployed by the NDO Plicator to invert the tissue and close the gastrotomy with full-thickness bites.…”
Section: Surgerymentioning
confidence: 99%
“…5 In fact, members of SAGES and ASGE recommended that access site closure reach 100% reliability before NOTES is approved for clinical trials in the United States. 5,15 Balloon-dilated gastrotomies in a porcine model have been observed to close spontaneously without specific efforts directed at closure. 16 However, incomplete access site closure in pigs has also been reported and resulted in complications as severe as frank peritonitis.…”
Section: Discussionmentioning
confidence: 99%